Misplaced Golgi Elements Produce Randomly Oriented Microtubules and Aberrant Cortical Arrays of Microtubules in Dystrophic Skeletal Muscle Fibers - Oddoux, Sarah; Randazzo, Davide; Kenea, Aster; Alonso, Bruno; Zaal, Kristien J. M.; Ralston, Evelyn (Frontiers in Cell and Developmental Biology, 2019)
Differentiated mammalian cells and tissues, such as skeletal muscle fibers, acquire an organization of Golgi complex and microtubules profoundly different from that in proliferating cells and still poorly understood. In adult rodent skeletal muscle, the multinucleated muscle fibers have hundreds of Golgi elements (GE), small stacks of cisternae that serve as microtubule-organizing centers. We are interested in the role of the GE in organizing a peculiar grid of microtubules located in the fiber cortex, against the sarcolemma. Modifications of this grid in the mdx mouse model of Duchenne muscular dystrophy have led to identifying dystrophin, the protein missing in both human disease and mouse model, as a microtubule guide. Compared to wild-type (WT), mdx microtubules are disordered and more dense and they have been linked to the dystrophic pathology. GE themselves are disordered in mdx. Here, to identify the causes of GE and microtubule alterations in the mdx muscle, we follow GFP-tagged microtubule markers in live mdx fibers and investigate the recovery of GE and microtubules after treatment with nocodazole. We find that mdx microtubules grow 10% faster but in 30% shorter bouts and that they begin to form a tangled network, rather than an orthogonal grid, right after nucleation from GE. Strikingly, a large fraction of microtubules in mdx muscle fibers seem to dissociate from GE after nucleation. Moreover, we report that mdx GE are mispositioned and increased in number and size. These results were replicated in WT fibers overexpressing the beta-tubulin tubb6, which is elevated in Duchenne muscular dystrophy, in mdx and in regenerating muscle. Finally, we examine the association of GE with ER exit sites and ER-to-Golgi intermediate compartment, which starts during muscle differentiation, and find it persisting in mdx and tubb6 overexpressing fibers. We conclude that GE are full, small, Golgi complexes anchored and positioned through ER Exit Sites. We propose a model in which GE mispositioning, together with the absence of microtubule guidance due to the lack of dystrophin, determines the differences in GE and microtubule organization between WT and mdx muscle fibers.